The Bra and Its Precursors:a structural and diachronic analysis (ModaPalavra e-periódico, 2018)
This paper presents a structural and diachronic analysis of the clothes worn to dress the female breasts. It privileged the literature review as a data source. These revealed that the configurational structures of the precursors -protossutians and corsets -were partially transferred to the bra. However, while the protossutians and corsets acted as maintainers of a status quo model of women who were not need worked, the bra contributed to a change in that paradigm. Its creation, adoption and popularization occurred in the early twentieth century, influenced by the demands of the world of work and the development of ready-to-wear.
Keywords: protossutian; corset; bra